Quantitative analysis of the phonon confinement effect in arbitrarily shaped Si nanocrystals decorated on Si nanowires and its correlation with the photoluminescence spectrum. (19th April 2015) - Ghosh, Ramesh; Pal, Arindam; Giri, P. K.
<x xml:space="preserve">Abstract</x> Arrays of single‐crystalline Si nanowires (NWs) decorated with arbitrarily shaped Si nanocrystals (NCs) are grown by a metal‐assisted chemical etching process using silver (Ag) as the noble metal catalyst. The metal‐assisted chemical etching‐grown Si NWs exhibit strong photoluminescence (PL) emission in the visible and near infrared region at room temperature. Quantum confinement of carriers in the Si NCs is believed to be primarily responsible for the observed PL emission. Raman spectra of the Si NCs decorated on Si NWs exhibit a red shift and an asymmetric broadening of first‐order Raman peak as well as the other multi‐phonon modes when compared with that of the bulk Si. Quantitative analysis of confinement of phonons in the Si NCs is shown to account for the measured Raman peak shift and asymmetric broadening. To eliminate the laser heating effect on the phonon modes of the Si NWs/NCs, the Raman measurement was performed at extremely low laser power. Both the PL and Raman spectral analysis show a log‐normal distribution for the Si NCs, and our transmission electron microscopy results are fully consistent with the results of PL and Raman analyses. We calculate the size distribution of these Si NCs in terms of mean diameter (D0) and skewness (σ) by correlating the PL spectra and Raman spectra of the as‐grown Si NCs decorated on Si NWs. Copyright © 2015 John Wiley & Sons, Ltd.